Completeness of Retail Pharmacy Claims Data: Implications for Pharmacoepidemiologic Studies and Pharmacy Practice in Elderly Adults - Polinski, Jennifer M. (2009)
BACKGROUND: In the elderly (those aged ≥65 years), retail pharmacy claims are used to study drug use among the uninsured after drug policy changes, to prevent drug drug interactions and duplication of therapy, and to guide medication therapy management. Claims include only prescriptions filled at one pharmacy location or within one pharmacy chain and do not include prescriptions filled at outside pharmacies, potentially limiting research accuracy and pharmacy-based safety interventions. OBJECTIVES: The aims of this study were to assess elderly patients’ pharmacy loyalty and to identify predictors of using multiple pharmacies. METHODS: Patients enrolled in the Pharmaceutical Assistance Contract for the Elderly pharmacy benefit program with corresponding Medicare claims in the state of Pennsylvania comprised the study cohort. Among patients with pharmacy claims from all pharmacies used in 2004–2005, a primary pharmacy was defined as the pharmacy where >50% of a patient’s prescriptions were filled. The number of pharmacies/chains used and prescriptions filled in 2005 was calculated. Predictors of using multiple pharmacies in 2005 were age, gender, race, urban residency, comorbidities, number of unique medications used, and number of prescriptions, which were all assessed in 2004. RESULTS: In total, pharmacy claims data from 182,235 patients (147,718 [81.1%] women; mean [SD] age 78.8 [7.1] years; 168,175 white; 76,580 residing in an urban zip code area) were included. In 2005, patients filled an average of 59.3 prescriptions, with 57.0 (96.1%) prescriptions having been filled at the primary pharmacy. Compared with patients who used <5 unique medications in 2004, patients who used 6 to 9 unique medications had 1.39 times (95% CI, 1.34–1.44), and patients who used 15 unique medications had 2.68 times (95% CI, 2.55–2.82) greater likelihood of using multiple pharmacies in 2005. Patients aged ≥85 years were 1.07 times (95% CI, 1.03–1.11) as likely to use multiple pharmacies compared with patients aged 65 to 74 years. CONCLUSIONS: This study found that patients aged ≥65 years were loyal to their primary pharmacy, offering reassurance to researchers and pharmacists who use retail pharmacy claims to evaluate and/or to improve safe and appropriate medication use among the elderly. Care should be used in analyzing claims from or managing the drug regimens of patients using many medications or patients aged ≥85 years; they are more likely to use multiple pharmacies and thus are more likely to have missing prescription information.